2021
DOI: 10.29303/jppipa.v7ispecialissue.1022
|View full text |Cite
|
Sign up to set email alerts
|

A Four-tier Diagnostic Instrument: An Analysis of Elementary Student Misconceptions in Science Topic

Abstract: Learning science in elementary schools encourages students to understand the natural environment more deeply, rationally, and scientifically. However, often the scientific concepts they believe about science topics are not in accordance with the scientific concepts they should be. This misconception is difficult for teachers to diagnose. Special instruments to identify and analyze students' misconceptions are needed. Therefore, this research aims to analyze the misconceptions of elementary school students on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In fact, the architecture of traditional houses built and lived in by the community is related to science or modern science (Fauzi et al, 2022). In other words, student-centered and contextually based science learning can reduce students' misconceptions about correct concepts according to experts (Sari et al, 2024).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the architecture of traditional houses built and lived in by the community is related to science or modern science (Fauzi et al, 2022). In other words, student-centered and contextually based science learning can reduce students' misconceptions about correct concepts according to experts (Sari et al, 2024).…”
Section: Resultsmentioning
confidence: 99%
“…Ibrahim (2019); Puja (2011) found that conceptual errors (misconceptions) and misunderstandings occurred among elementary school teachers. Meanwhile Kartimi et al (2021); Faridah et al (2020); Munawaroh & Falahi (2016) found misconceptions in elementary school students, Ariandini et al (2013) found misconceptions in junior high school students. Wulandari et al (2021); Fauzannur et al (2022) found misconceptions in senior high school students.…”
Section: A Introductionmentioning
confidence: 99%
“…When elementary school teachers experience misconceptions, the impact is that students also experience misconceptions (Farida et al, 2020;Mawaddah et al, 2020;Kartimi et al, 2021). A survey on misconceptions has been launched in 2021 on elementary school teachers spread across 25 provinces, who are currently students in the Teacher Professional Education (PPG) study program at Nahdlatul Ulama University Surabaya (Unusa) totaling 268 people.…”
Section: A Introductionmentioning
confidence: 99%
“…A student who actively constructs knowledge about various phenomena during his life without the participation of a teacher often has a different view from scientists. So, teachers must be able to distinguish the characteristics of students who lack knowledge, misconceptions, or other profiles to overcome problems by designing learning as a solution (Juita et al, 2023;Kartimi et al, 2021;Köse, 2008; IJEE. P-ISSN: 2579-7158 E-ISSN: 2549-6050 Margunayasa et al, 2021;Putri, Widodo, & Rusyati, 2021;Resbiantoro, Setiani, & Dwikoranto, 2022;Soeharto et al, 2019).…”
Section: Introductionmentioning
confidence: 99%